ACCOUNT REPRESENTATIVE JEMBATAN PENGHUBUNG BAGI KEPATUHAN WAJIB PAJAK - Eddy - Suryanto HP (Universitas Slamet Riyadi, 2013)
ABSTRACT Taxpayers to make tax reform as partners with the implementation of the Directorate General of Taxation Tax Administration System Modern spawned new Account Representative positions in charge of supervising compliance with tax obligations, implement guidance and an appeal to taxpayers and potential exploration. Keywords: account representative, taxpayers.